Pengaruh Harga dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Usaha Mie Gacoan di Bandar Lampung - Maria Roma Ito Sitompul; Indriati Agustina Gultom (Komunitas Dosen Indonesia, 2025)
The objective of this study is to determine the extent to which pricing and service quality influence customer satisfaction within the Gacoan business in Bandar Lampung. The research was conducted at Mie Gacoan Bandar Lampung, located at Jl. Gajah Mada No. 170, Kota Baru, Kec. Tanjung Karang Timur, Bandar Lampung City, Lampung. This study employed a quantitative approach and an associative research method. The population under consideration consists of customers who have utilized Mie Gacoan's services, with an estimated 12,000 visits per month. The sample size was determined using the Slovin formula with a margin of error set at 10%, resulting in a total of 100 respondents. A purposive sampling technique was applied to select participants who met specific criteria. Primary data were gathered through the distribution of questionnaires using a Likert scale as the measurement tool. The findings of this research are expected to provide deeper insights into the factors that influence customer satisfaction at Mie Gacoan Bandar Lampung.